Critical updates on oral insulin drug delivery systems for type 2 diabetes mellitus - Chan Yew Low; Wei Ling Gan; Su Jeat Lai; Rachel Su-May Tam; Jie Fei Tan; Stefanie Dietl; Lay Hong Chuah; Nicolas Voelcker; Athirah Bakhtiar (Journal of Nanobiotechnology)
Abstract Type 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by insulin resistance, leading to elevated blood sugar levels. Exogenous insulin can counteract the diminished response to insulin and effectively controlling blood glucose levels, thereby minimizing diabetes-related complications. However, given the injectable nature of exogenous insulin, apprehensions regarding its safety and the difficulties associated with its administration have hindered its widespread and prompt utilization. In this context, advanced oral insulin formulations can improve medication adherence in patients with diabetes and enhance their quality of life. Over the last 20 years, sophisticated pharmaceutical technologies have been utilized to provide insulin through oral formulations. Despite the limited absorption of oral insulin, these studies have demonstrated encouraging outcomes in translating clinical discoveries into commercialization. This review examines the advancements of several oral insulin formulations in preclinical and clinical trials, their effectiveness and safety characteristics, and potential implications for future treatment options. Graphical Abstract